Extraction of Au(III), Pt(IV), and Pd(II) from Aqueous Media with Deep Eutectic Solvent Dissolved in n-Heptane as Extractant - Pius Dore Ola; Michiaki Matsumoto (Universitas Gadjah Mada, 2023)
Due to the scarcity, studying precious metals extraction such as gold, platinum, and palladium is very critical. Solvent extraction is one of the established methods due to its simplicity and quickness but the low operational cost. In this study, a deep eutectic solvent (DES) consisting of decanoic acid and lidocaine in the molar ratio of 2:1 was applied as an extractant to extract Au(III), Pt(IV), and Pd(II) from aqueous media. Au(III) was solvated and extracted with DES in the form of AuCl3. Pd(II) was extracted by the cation exchange reaction between Pd2+ and H+. Complete extraction of Au(III) 98.2% and Pd(II) 100% can be achieved using 500 and 300 g/L DES, respectively. This finding opens new opportunities for improving Au(III) and Pd(II) extraction using an environmental friendly and inexpensive extractant.